Memperkenalkan Reaksi Asam Basa Melalui Percobaan Asam Cuka dan Soda Kue di Lingkungan Madrasah Ibtidaiyah Ihya Ulumiddin Kota Banjarmasin - Gusti Hadiatus Solehah; Khairullah Khairullah; Muhammad Arbain (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This Community Service Activity (PKM) aims to introduce the concept of acid-base reactions to the students of Madrasah Ibtidaiyah Ihya Ulumiddin in Banjarmasin through a simple experiment involving vinegar and baking soda. The selection of this material is based on the importance of early understanding of basic chemistry concepts to build critical and analytical thinking skills in children. In this activity, students are introduced to the phenomenon of acid-base reactions directly through a safe and simple experiment that can be conducted in the madrasah environment. The students are encouraged to observe the changes that occur when vinegar (acetic acid) is mixed with baking soda (sodium bicarbonate), which produces carbon dioxide gas. With this experimental-based learning approach, it is hoped that students will better understand and apply the concept of acid-base in daily life and foster their interest in natural sciences. This activity is expected not only to enrich students' scientific knowledge but also to provide an enjoyable and engaging learning experience beyond the theories taught in class.